The invisible made visible: Theological and philosophical conceptions of God’s image in Jewish and Greco-Roman contexts - Tanasyah, Yusak (Institut Agama Kristen Negeri Toraja, 2025)
This paper examines how the concept of the image of the invisible God was understood in Jewish and Greco-Roman traditions. It explores Jewish theological ideas rooted in Hebrew Scriptures and later Jewish writings, which emphasize a transcendent yet immanent God. In contrast, Greco-Roman thought, shaped by Platonic and Stoic philosophies, conceptualized the divine through reason, logos, and cosmic order, often expressed through anthropomorphic deities or philosophical ideals. The study highlights how these differing views intersected, particularly during the Second Temple period, influencing early Christian theology—especially the idea of Jesus as the visible expression of the invisible God. By analyzing religious texts and philosophical works, the paper sheds light on ancient understandings of divinity and their lasting impact on conceptions of the divine-human relationship. By analyzing these diverse perspectives, the paper aims to provide a comprehensive understanding of how the image of the invisible God was perceived and represented across different cultures and epochs. This exploration not only enriches our knowledge of ancient religious thought but also offers insights into the enduring questions about the nature of divinity and humanity’s relationship to the divine.